Knowledge Valorization in the Cognitive Capitalism - Miguez, Pablo Fernando (2013)
This work subscribes to approaches that defends the idea of a rupture in the long-term dynamic of capitalism. This rupture it is linked to the passage of the industrial capitalism to a new historical system of accumulation. The cognitive division of work suppose a new logic of valorization that not replace but overlap to the logic of industrial capitalism. The role of knowledge in the process of valorization is a fundamental resource to understand the historical breakthrough in the accumulation process. We propose a historical reading of this dynamics around two main aspects of the accumulation of capital: the creation of value, the relationship between work and means of production and in second place the appropriation of value, where we can see in jeopardy the capture of the innovation rent.